Convergent syntheses of LeX analogues - Wang, An; Hendel, Jenifer; Auzanneau, France-Isabelle (Beilstein Journal of Organic Chemistry, 2010)
The synthesis of three Lex derivatives from one common protected trisaccharide is reported. These analogues will be used respectively for competitive binding experiments, conjugation to carrier proteins and immobilization on gold. An N-acetylglucosamine monosaccharide acceptor was first glycosylated at O-4 with a galactosyl imidate. This coupling was performed at 40 °C under excess of BF3·OEt2 activation and proceeded best if the acceptor carried a 6-chlorohexyl rather than a 6-azidohexyl aglycon. The 6-chlorohexyl disaccharide was then converted to an acceptor and submitted to fucosylation yielding the corresponding protected 6-chlorohexyl Lex trisaccharide. This protected trisaccharide was used as a precursor to the 6-azidohexyl, 6-acetylthiohexyl and 6-benzylthiohexyl trisaccharide analogues which were obtained in excellent yields (70–95%). In turn, we describe the deprotection of these intermediates in one single step using dissolving metal conditions. Under these conditions, the 6-chlorohexyl and 6-azidohexyl intermediates led respectively to the n-hexyl and 6-aminohexyl trisaccharide targets. Unexpectedly, the 6-acetylthiohexyl analogue underwent desulfurization and gave the n-hexyl glycoside product, whereas the 6-benzylthiohexyl analogue gave the desired disulfide trisaccharide dimer. This study constitutes a particularly efficient and convergent preparation of these three Lex analogues.
Keywords: Birch reduction; convergent synthesis; desulfurization; Lewis X